UJI EFEKTIVITAS MINYAK ATSIRI DAUN KEMANGI (Ocimum sanctum Linnaeus) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus - Sutriswanto, Sutriswanto; Kurniawati, Fifi; Sulistiyowati, Endah; Syopingi, Syopingi (poltekkes kemenkes pontianak, 2023)
Herbal plants are plants that have a function in health as medicine. There are lots of plants that can be used as herbal medicine, one of which is the basil plant. Basil leaves contain chemical compounds including saponins, flavoniods, tannins and essential oils. The main ingredient in basil is essential oil. The essential oil of basil has the potential as an antibacterial. The purpose of this study was to analyze the effectiveness of basil leaf essential oil in inhibiting the growth of Staphylococcus aureus bacteria based on the standard antibiotic inhibition zone according to CLSI. This study used a quasi-experimental research design (Quasy Experiment) with a purposive sampling technique. The population of this research is basil (Ocimum sanctum Linnaeus). The samples used were basil essential oil concentrations of 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44% and 46%. Then tested the antibacterial activity using the diffusion method. Based on research the average inhibition zone at a concentration of 30% inhibition zone formed was 15 mm, 32% concentration was 18 mm, 34% concentration was 16.67 mm, 36% concentration was 15.67 mm, 38% concentration was 17.67 mm, 40% concentration was 22.33 mm, 42% concentration was 16.33 mm, 44% concentration was 18 mm, 46% concentration of 21.33 mm. The conclusion in this study is that there is effectiveness of basil leaf essential oil with the interpretation of Sensitive results in inhibiting the growth of Staphylococcus aureus bacteria by the diffusion method based on the standard antibiotic inhibition zone according to CLSI.